Bomanjee Hormarjees Building - Ghosh, Ayan (2023)
The old name of Horniman Circle on the Bomanjee Hormarjees Building. The Parsi after whom the building is named, Bomanjee Hormarjees Wadia (d. 1862) was a member of the Bombay Native Education Society and served on the board of Elphinstone Institution. His house was a popular meeting place to exchange gossip, and thus earned the epithet 'Gup House'.